CLINICAL AND EXPERIMENTAL STUDY OF THE EFFECTS OF THE LONG-TERM ACTION OF SODIUM FLUORIDE ON THE MOLECULAR-GENETIC MECHANISMS OF BONE TISSUE REMODELING - Анна Геннадьевна Жукова; Елена Александровна Семенова; Татьяна Константиновна Ядыкина; Лариса Геннадьевна Горохова; Мария Сергеевна Бугаева (Медицина в Кузбассе)
Objective. Clinical and experimental study of the effects of the long-term action of sodium fluoride on the molecular-genetic mechanisms of bone tissue remodeling.